2021
DOI: 10.1093/ejcts/ezab144
|View full text |Cite
|
Sign up to set email alerts
|

Propensity score-based analysis of long-term follow-up in patients supported with durable centrifugal left ventricular assist devices: the EUROMACS analysis

Abstract: OBJECTIVES The HeartWare HVAD (HW) and the HeartMate3 (HM3) are presently the most commonly used continuous-flow left ventricular assist devices worldwide. We compared the outcomes of patients supported with either of these 2 devices based on data from the EUROMACS (European Registry for Patients with Mechanical Circulatory Support). METHODS A retrospective analysis of the survival and complications profile in propensity scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
46
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 20 publications
8
46
1
Order By: Relevance
“…Although it did not reach a statistical level of significance, a trend toward lower daily beta blocker doses were observed in patients with the HM3 compared to those with the HVAD device (3.75 mg vs. 5 mg; p = 0.085). We hypothesized that the results of previous clinical trials demonstrating the superiority of the HM3 device with respect to thromboembolic events [ 11 , 12 , 13 , 14 ] may have led to differences in the stringency of blood pressure management and thus lower doses of beta blockers in patients implanted with the HM3. Thus, our results suggest that it is not the device design per se, but differences in best practices in patient care that lead to a lower incidence of RHF in patients with the HM3 device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it did not reach a statistical level of significance, a trend toward lower daily beta blocker doses were observed in patients with the HM3 compared to those with the HVAD device (3.75 mg vs. 5 mg; p = 0.085). We hypothesized that the results of previous clinical trials demonstrating the superiority of the HM3 device with respect to thromboembolic events [ 11 , 12 , 13 , 14 ] may have led to differences in the stringency of blood pressure management and thus lower doses of beta blockers in patients implanted with the HM3. Thus, our results suggest that it is not the device design per se, but differences in best practices in patient care that lead to a lower incidence of RHF in patients with the HM3 device.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a less invasive surgical implantation strategy has been suggested to have a protective effect on the development of RHF after LVAD implantation [ 10 ]. Recent studies have suggested the superiority of the HeartMate 3 (HM3) (Abbott Inc., Chicago, IL, USA) over the HVAD (Medtronic Inc., Minneapolis, MN, USA) device in terms of the occurrence of thromboembolic events [ 11 , 12 , 13 , 14 ]; however, other analyses have failed to identify substantial differences [ 15 ]. A possible superiority of the HM3 vs. HVAD device in terms of the development of RHF has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation for the increased stroke risk is that anticoagulation to an ACT of 180 s during LVAD implantation on va-ECLS or off-pump may be insufficient. Furthermore, two recent studies based on retrospective analyses of major data registries showed an increased risk for neurological adverse events in patients with HeartWare HVAD LVADs (HW; Medtronic, Minneapolis, MN, USA) compared to HeartMate 3 (HM3; Abbott, Chicago, IL, USA) 13,14 ; however, there was no difference in the incidence of neurological adverse events during the short-term follow up. Our analysis identified female sex as a possible pre-existing risk factor 15 for perioperative or postoperative ischemic stroke (<30 days).…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Moreover, HVAD patients experienced more device malfunction, pump thrombosis and neurological dysfunction. 7 These studies comprise the largest propensity matched cohorts of the two LVADs to date. Although sound statistical methods were used, differences in patient selection and management, surgeons' individual preferences and local protocols for the different devices may still have influenced the results.…”
Section: Intermacs and Euromacs Analysesmentioning
confidence: 99%
“…However, in the past few years, the amount of de novo HM3 implants have outnumbered the HVAD implants 5 . Recently, two observational studies from the Interagency Registry for Mechanically Assisted Circulatory Support (INTERMACS) and the European Registry for Patients on Mechanical Circulatory Support (EUROMACS) have described worse outcomes for HVAD vs. HM3 implanted patients 6,7 . In addition, in 2020 Medtronic issued a Safety Notice regarding the HVAD related to a delayed or even failure to restart the LVAD after controller exchange.…”
mentioning
confidence: 99%